PENGARUH BAURAN PROMOSI TERHADAP VOLUME PENJUALAN PADA PT. VIVA VICTORY ABADI - Komarudin Komarudin; Hendro Setyono (Universitas Ahmad Dahlan, 2016)
The purpose of this study was to determine the effect on promotion mix on volume sales PT Viva Victory Abadi. Results are expected to be a consideration for managers PT Viva Victory Abadi in determining the promotional mix effect on sales of property, as well as using some other variables of the promotion mix. The study was based on data usage all promotional costs incurred as well as the sale of the property from PT Viva Victory Abadi in the last two years. The data is then processed using multiple linear regression method in SPSS. The results obtained prove not the absence of significant promotional mix on volume sales of PT Viva Victory Abadi.